2-hydroxyethyl Cellulose-ammonium Thiocyanate Solid Biopolymer Electrolytes: Ionic Conductivity And Dielectric Studies - Muhamad Amirullah Ramlli; Hilmun Kamarudin; Mohd Ikmar Nizam Mohamad Isa (Penerbit UMT, 2024)
Indexed by SCOPUS/ERA/MYCITE